“There is a Bit of Grace Missing”: Understanding Non-use of Mobile Robotic Telepresence in a Global Technology Company - Boudouraki, Andriana; Reeves, Stuart; Fischer, Joel; Rintel, Sean (TAS 2023, 2023)
Mobile robotic telepresence technology may be a potential solution to hybrid communication as it allows remote attendees embodied movement in space. Yet, there is little exploration into how its affordances fit with the practices and needs of workplaces. This paper presents findings from interviews conducted following a discontinued deployment of telepresence robots at the offices of a global technology company. The findings indicate that in this case 1) The knowledge workers were equipped to manage hybrid work, 2) the robots offered limited perceived value, and 3) the robots were a poor fit to the knowledge workers’ physically distributed workflows. Drawing workflows and non-use literature, we explore how features of the technology failed to align with the office’s work practices and needs, and discuss the implications for evaluating the low use of robotic telepresence.